2023
DOI: 10.3390/life13020548
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Bacteria Isolated from Marketed Sparus aurata and Penaeus indicus Sea Products: Antibiotic Resistance Profiling and Evaluation of Biofilm Formation

Abstract: Background: Marketed fish and shellfish are a source of multidrug-resistant and biofilm-forming foodborne pathogenic microorganisms. Methods: Bacteria isolated from Sparus aurata and Penaeus indicus collected from a local market in Hail region (Saudi Arabia) were isolated on selective and chromogenic media and identified by using 16S RNA sequencing technique. The exoenzyme production and the antibiotic susceptibility patterns of all identified bacteria were also tested. All identified bacteria were tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Additionally, bacteria were isolated from aurus and Penaeus indicus collected from local markets in Hail region, Saudi Arabia. Drug sensitivity tests showed that there was multidrug resistance [42]. The use and misuse of antimicrobials can lead to a rapid increase in the frequency of bacterial resistance; antibiotic resistance has become a major problem in veterinary and human medicine [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bacteria were isolated from aurus and Penaeus indicus collected from local markets in Hail region, Saudi Arabia. Drug sensitivity tests showed that there was multidrug resistance [42]. The use and misuse of antimicrobials can lead to a rapid increase in the frequency of bacterial resistance; antibiotic resistance has become a major problem in veterinary and human medicine [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Total DNA was extracted from overnight 24 h bacterial culture growth. The guanidine chloride procedure was used for DNA extraction as detailed previously [ 31 ]. DNA quality and quantity were determined by gel-electrophoresis and Qubit (Thermo Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The sequencing of the genomes of the selected strains was done by Novogene Company (Hong Kong, China) using Illumina HiSeq 2500 (Illumina, San Diego, CA, USA), and paired-end 150 bp reads with 100X coverage were achieved. Genome sequences were reassembled using SPAdes version 3.7 software [ 31 , 32 ]. Plasmids were assembled using plasmidSPAdes tool v3.15.4, applying different k-mer sizes (21, 33, and 55) [ 33 ].…”
Section: Methodsmentioning
confidence: 99%